2009
DOI: 10.1111/j.1095-8649.2009.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways during marine fish egg hydration: the role of aquaporins

Abstract: The pre-ovulatory hydration of the oocyte of marine teleosts, a unique process among vertebrates that occurs concomitantly with meiosis resumption (oocyte maturation), is a critical process for the correct development and survival of the embryo. Increasing information is available on the molecular mechanisms that control oocyte maturation in fish, but the identification of the cellular processes involved in oocyte hydration has remained long ignored. During the past few years, a number of studies have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 102 publications
2
12
0
Order By: Relevance
“…Regarding the free living aquatic algae of this study we note that in some species of fish, MIPs have an important physiological function, regulating the buoyancy of the egg by adjusting the water content and thereby controlling the depth and hence the milieu for the developing egg [41,42]. It seems possible that a similar regulation can occur in free living algae in order to find optimal conditions for photosynthesis, uptake of nutrients, transport by currents or possibly to escape predators.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the free living aquatic algae of this study we note that in some species of fish, MIPs have an important physiological function, regulating the buoyancy of the egg by adjusting the water content and thereby controlling the depth and hence the milieu for the developing egg [41,42]. It seems possible that a similar regulation can occur in free living algae in order to find optimal conditions for photosynthesis, uptake of nutrients, transport by currents or possibly to escape predators.…”
Section: Discussionmentioning
confidence: 99%
“…The small peptides and free amino acids generated during maturational yolk processing, along with inorganic ions, act as osmotic effectors that drive an influx of water into the oocyte [26,32,52]. Water diffuses through aquaporins in the oocyte membrane [40,41], and this influx of water results in oocyte hydration and proper egg buoyancy. This hydration also provides metabolic water for dilution of embryonic waste products and an increased egg volume to allow an adequate space for embryonic development.…”
Section: Ovarian Maturation and Proteolysis Of Yolk Proteinsmentioning
confidence: 99%
“…Despite this degeneracy, Aqp1ab has been found to play a conserved role in the oocyte hydration of teleosts (reviewed by Cerdà, 2009; Finn and Fyhn, 2010). The novel role of Aqp1ab in oocyte hydration was first suggested for gilthead seabream (Fabra et al, 2005), and has recently been experimentally demonstrated in the acanthomorph teleost Atlantic halibut (Zapater et al, 2011).…”
Section: Duplication and Dual Neofunctionalization Of Piscine Aquaporinsmentioning
confidence: 99%